Differential effects of Western diet and traumatic muscle injury on skeletal muscle metabolic regulation in male and female mice - Junwon Heo; Albino G. Schifino; Jennifer McFaline‐Figueroa; David L. Miller; Jessica R. Hoffman; Emily E. Noble; Sarah M. Greising; Jarrod A. Call (Wiley, 2023)
Abstract Background This study was designed to develop an understanding of the pathophysiology of traumatic muscle injury in the context of Western diet (WD; high fat and high sugar) and obesity. The objective was to interrogate the combination of WD and injury on skeletal muscle mass and contractile and metabolic function. Methods Male and female C57BL/6J mice were randomized into four groups based on a two‐factor study design: (1) injury (uninjured vs. volumetric muscle loss [VML]) and (2) diet (WD vs. normal chow [NC]). Electrophysiology was used to test muscle strength and metabolic function in cohorts of uninjured + NC, uninjured + WD, VML + NC and VML + WD at 8 weeks of intervention. Results VML‐injured male and female mice both exhibited decrements in muscle mass (−17%, P < 0.001) and muscle strength (−28%, P < 0.001); however, VML + WD females had a 28% greater muscle mass compared to VML + NC females (P = 0.034), a compensatory response not detected in males. VML‐injured male and female mice both had lower carbohydrate‐ and fat‐supported muscle mitochondrial respiration (JO2) and less electron conductance through the electron transport system (ETS); however, male VML-WD had 48% lower carbohydrate‐supported JO2 (P = 0.014) and 47% less carbohydrate‐supported electron conductance (P = 0.026) compared to male VML + NC, and this diet-injury phenotype was not present in females. ETS electron conductance starts with complex I and complex II dehydrogenase enzymes at the inner mitochondrial membrane, and male VML + WD had 31% less complex I activity (P = 0.004) and 43% less complex II activity (P = 0.005) compared to male VML + NC. This was a diet-injury phenotype not present in females. Pyruvate dehydrogenase (PDH), β‐hydroxyacyl‐CoA dehydrogenase, citrate synthase, α‐ketoglutarate dehydrogenase and malate dehydrogenase metabolic enzyme activities were evaluated as potential drivers of impaired JO2 in the context of diet and injury. There were notable male and female differential effects in the enzyme activity and post‐translational regulation of PDH. PDH enzyme activity was 24% less in VML‐injured males, independent of diet (P < 0.001), but PDH enzyme activity was not influenced by injury in females. PDH enzyme activity is inhibited by phosphorylation at serine‐293 by PDH kinase 4 (PDK4). In males, there was greater total PDH, phospho‐PDHser293 and phospho‐PDH‐to‐total PDH ratio in WD mice compared to NC, independent of injury (P ≤ 0.041). In females, PDK4 was 51% greater in WD compared to NC, independent of injury (P = 0.025), and was complemented by greater phospho‐PDHser293 (P = 0.001). Conclusions Males are more susceptible to muscle metabolic dysfunction in the context of combined WD and traumatic injury compared to females, and this may be due to impaired metabolic enzyme functions.